Penggunaan Metode Forensik Dalam Pengungkapan Kejadian Klaim Asuransi Kebakaran - Ferdinand, Sean Michael; Awaloedin, Mulawarman; Nasyubun, M (Lentera Dua Indonesia, 2023)
When an insurance claim occurs, there is often a difference of opinion between the insurer and the insured in interpreting the contents of the policy. In order to resolve claim disputes, according to the clauses in the policy, an opinion from an independent third party is needed. The purpose of third party involvement is to provide an opinion from another point of view. In this research, it is described how third parties are involved in resolving an insurance claim. Starting from the incident report, it was reported that a fire had occurred at latitude coordinates 7°25'26